EFL Teachers’ Considerations in Developing Online Teaching Materials - Ivani Noviarani; Didi Suherdi; Eri Kurniawan (Journal of English Language Teaching and Linguistics, 2021)
The sudden necessity of studying from home forced teachers to immediately readjust their teaching materials into the online teaching materials form. However, online tools for language teaching that can be used by teachers as sources and learning media in their teaching materials vary widely. Therefore, the present study purposed at understanding experienced English as Foreign Language (EFL) teachers’ considerations in developing online teaching materials amid the COVID-19 pandemic. The data collected through qualitative case study research design. The data gathered through document analysis and interview. The data analyzed by the form proposed by Miles and Huberman (1994). The result of the study reveals that there are 3 out of 8 principles of teaching materials that teachers take into account; giving the students fresh input, facilitating students learning style and attitudes, and contain audio-visual media. There is also found 2 others principle that does not really considered as a matter in developing online teaching materials; achieve impact by requiring and facilitating learner self-investment and provide opportunities to give feedback.